Technology strategy in family business: a new avenue for research. (1st January 2013) - Bigliardi, Barbara; Cassia, Lucio; De Massis, Alfredo; Frattini, Federico
While studies of technology strategy and family business have to a great extent developed independently, there are some clues that they are now moving closer to each other. The purpose of this special issue is to contribute to a growing scholarly interest in research that integrates the fields of technology strategy and family business. We begin this introductory article by providing a brief overview of some theoretical reasons underlying the distinctive behaviour of family firms as regards technology strategy. We then propose a framework for addressing the role of family firms in technology strategy that highlights the input-activities-output-performance nature of technology strategy in family business. We conclude by introducing the seven papers that are included in this special issue using the framework developed to position the papers and thereby to reveal their respective contributions and their advancement of existing knowledge.